A Meta-Analysis Study of the Effectiveness of Inquiry-Based Learning in Improving Science Literacy and Elementary School Students' Learning Outcomes - Ayu Safitri; Septia Fairis Ramadhani; Agung Setyawan (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to examine the effectiveness of the Inquiry-Based Learning (IBL) model in improving elementary school students' learning outcomes and scientific literacy. Using a literature review and meta-analysis approach, this study reviewed journal articles published between 2018 and 2025 that implemented the IBL model, focused on elementary school students, and discussed learning outcomes and scientific literacy. Six studies met the inclusion criteria. The results showed that IBL effectively improved students' learning outcomes and scientific literacy, with an average increase of 19.73%. The highest increase was 30.00%, and the lowest was 7.9%. These findings indicate that IBL encourages students to think critically and analytically, actively engage in learning, and construct knowledge through direct experience. Overall, IBL is an effective and relevant model to support scientific literacy and learning outcomes in 21st-century education.